Study on the Seismic Response and Aseismic Measure of Fault-Crossing Tunnels under Combined Action of Fault Dislocation and Seismic Motions - Jieli Li; Zhiguo Ma; Ruohan Li; Zhensheng Cao; Shaoqiang Zhang (Shock and Vibration)
Seismic investigation revealed that a fault fracture zone is one of the most vulnerable areas of mountain tunnels in earthquakes. For the tunnel crossing secondary fault, the fault may be permanently dislocated by the causative faults during earthquakes, making the tunnel subject to combined action of seismic motion and fault dislocation, which makes the seismic response of the tunnel more complicated. In order to investigate the seismic response of fault-crossing tunnels in this case and explore the suitability of different aseismic measures, three-dimensional numerical models with different widths of faults and different aseismic measures were developed in this study. By inputting accelerogram considering permanent displacements, the seismic responses of fault-crossing tunnels under the combined action of seismic motion and fault dislocation were simulated. The results showed that the acceleration and stress of the tunnel-crossing narrow fault are larger than those crossing wide faults during earthquakes. Grouting reinforcement can reduce the acceleration and stress of the tunnel within the fault during earthquakes, while flexible joints will increase the acceleration of the tunnel within the fault and increase the stress of the tunnel-crossing wide fault. For fault-crossing tunnels, if the fault width is narrow than the tunnel diameter, the best aseismic measure installs grouting reinforcement and flexible joints; if the fault width is wider than 10 times of the tunnel diameter, the best aseismic measure installs grouting reinforcement.